Política educacional e poder local: análise das repercussões do Programa de Erradicação do Trabalho Infantil na educação de municípios pernambucanos - Rosilda Ferreira Arruda (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
In this paper, the impact of the implementation of the Programme for the Eradication of Child Labour (PECL) on thirteen cities in the State of Pernambuco, Brazil, is analysed focusing on the period between November 1997 and January 2000. Child labour in Brazil and specifically in the state of Pernambuco is characterised along with a description of how the Programme was created. The results of the research reveal the Programmes difficulties in achieving its goal of eradicating child labour, despite its temporary suspension in those cities under analysis. The educational results reveal that despite the positive impact of the Programme in decreasing the number of school dropouts, in pedagogical terms, efforts are still needed to improve the quality of education and the levels of student learning.